Nature’s Services and Contributions: The Relational Value of Childhood Nature Experience and the Importance of Reciprocity - Beery, Thomas H.; Lekies, Kristi S. (Frontiers in Ecology and Evolution, 2021)
People depend on functioning ecosystems to meet human needs and support well-being across the life span. This article considers the interest in ecosystem services valuation, the growing interest in the benefits of nature experience for children, and ways to bridge these perspectives. We focus on embodied childhood nature experiences: the physical and multisensory experiences that intertwine child and nature. Additionally, we highlight the reciprocal quality of nature and child experience relationship as an example of how this relationship goes beyond the instrumental and demonstrates relational value. Underlying this perspective is the belief that children need to be better represented in the perception and action of ecosystem valuation in environmental policy.